Traces of Māturīdīsm in the ‘Ulamā’s Works in Nusantara in the Seventeenth Until Nineteenth Centuries - Muhamad Bindaniji (Faculty of Islam Nusantara University of Nahdlatul Ulama Indonesia (UNUSIA) Jakarta., 2020)
Theological discourse in Nusantara is always associated with two varieties of Ash‘arīsm and Māturīdīsm. Nevertheless, Ash‘arīsm became the dominant theological discourse for Muslim people of Nusantara at least since the seventeenth century—or more—which brought by ‘Ulamā’s. There are some obscurity concerning the history of Māturīdīsm about the carriers and teachings developed. Thus it is oﬅen assumed that the theological discourse that developed in Nusantara since Islam entered and developed just an Ash‘arīsm and ignored other theology [Māturīdīsm]. This study would prove that Māturīdīsm developed along with the development of Ash‘arīsm through the global networks of the Nusantara ‘Ulamā around theological discourse in the Muslim world. This study attempts to provide the justiﬁcation of Māturīdīsm that developed in Nusantara as well as provide a new perspective about method of theology for Muslim people of Nusantara. The focus of this study is to explore the intellectual treasures of ulama’s works in Nusantara who lived in the period of the seventeentah until nineteenth centuries. This study concludes that theological discourse in Nusantara is a continuous form of global theological discourse that developed in the Islamic world, where the emerging theological discourse always associated on two varieties of Ash‘arīsm and Māturīdīsm which later became known as Sunnīsm. In this context, the discourse of Māturīdīsm developed in Nusantara is seen as a method of thinking that is in tune with the tradition of Sunnīsm which emphasizes the elements of moderation and balance in theology. Keywords: Theology, Sunnī, Ash‘arīsm, Māturīdīsm, ‘Ulama, Nusantara Reference: Abdullah, Muhd Saghir, Sheikh Muhammad Arsyad al-Banjari: Pengarang Sabilal Muhtadin. Kuala Lumpur: Khazanah Fathimiyah, n.d. Abū ‘Udhba, al-Rawḍat al-Bahīyah fī-mā Bayn al-Ashā’irah wa al-Māturīdīyah. Hyderabad: n.p, 1322 H. Arshād, M. al-Banjārī, Tuḥfah al-Rāghibīn fī Bayān Ḥaqā’iq Īmān al-Mu’minīn, MS collection of PNRI Jakarta, v.d.w. 37. ________, Durr al-Nafis fī ‘Ilm al-Tawḥīd. Singapura: al-Haramayn, 2005. Ash‘ari, Hashim, Risālah Ahl al-Sunna wa al-Jamā‘a. Jombang: al-Maktabah al-Islāmī, n.d. Attas, M. Naquib al-, The Oldest Known Malay Manuscript: A 16th Century Malay Translation of the ‘Aqā’id of al-Nasafī. Kuala Lumpur: University of Malaya Press, 1988. _______, Al, Commentary on the Ḥujjat al-Ṣiddīq of Nūr al-Dīn al-Rānīrī. Kuala Lumpur: Misnistry of Culture, 1986. _______, The Mysticism of Hamzah Fansuri. Kuala Lumpur: University of Malaya Press, 1970. Azra, Azyumardi, Jaringan Ulama Timur Tengah dan Kepulauan Nusantara Abad XVII & XVIII. Jakarta: Kencana, 2013. Baghdādī, Abd al-Qāhir bin Ṭāhir al-, al-Farq Bayn al-Firāq. Beirut: Dār al-Kutub al-‘Ilmīyah, 2009. Bantanī, Nawawī al-, Fatḥ al-Majīd fī Sharḥ al-Durr al-Farīd fī ‘Ilm al-Tawḥīd. Bandung: al-Ma‘ārif, n.d. _______, Nihāyat al-Zayn fī Irshād al-Mubtadi‘īn. Beirut: Dār al-Kutub al-‘Ilmīyah, 2002. Bazdawī, Abū al-Yusr Muhammad al-, Kitāb Uṣūl al-Dīn. Cairo: al-Maktabah al-Azharīyah, 2003. Ceric, Mustafa, Roots of Synthetic Theology in Islam: A Study of the Theology of Abu Mansur al-Maturidi. Kuala Lumpur: ISTAC, 1995. Drewes, G.W.J., “Further Data Concerning ‘Abd al-Samad al-Palimbani”, in Bijdragen tot de Taal-, Land- en Volkenkunde 132, No. 2/3 (1976). _______, The Admonitions of Seh Bari: A 16th Century Javanese Muslim Text. Den Haag: Martinus Nijhoff, 1969. Effendi, Djohan, Pembaruan Tanpa Membongkar Tradisi. Jakarta:Kompas, 2012. Eissa, Mohamed Ahmed Abdelrahman, The Jurist and the Theologian: Speculative Theology in Shāfi‘ī Legal Theory. New York: Gorgias Press, 2017. Fādānī, Yāsīn al-, al-'Iqd al-Farīd min Jawāhir al-Asānīd. Surabaya: Dār al-Saqāf, 1981. Fathurahman, Oman, Katalog Naskah Tanoh Abee Aceh Besar. Jakarta: Komunitas Bambu & PPIM, 2010. Ghurābah, Ḥamūdah, Abū Ḥasan al-Ash‘arī. Cairo: Majma‘ al-Buḥūth al-Islāmīyah, 1993. Griffel, Frank, Al-Ghazālī’s Philosophical Theology. New York: Oxford University Press, 2009. Hasan, Noorhaidi, “Muhammad Arshad al-Banjari (1710-1812) and the Discourse of Islamization in the Banjar Sultanate”, thesis M.A. Leiden: Leiden University, 1999. _______, “The Tuḥfah al-Rāghibīn: the Work of Abdul Samad al-Palimbani or of Muhammad Arsyad al-Banjari?”, in Bijdragen tot de Tall-, Land-en Volkenkunde (BKI) 161-3, 2007. Hasjmy, Ali, Syi’ah dan Ahlussunnah; Saling Rebut Pengaruh dan Kekuasaan Sejak Awal Sejarah Islam di Kepulauan Nusantara. Surabaya: PT.Bina Ilmu, 1983. Hasyim, Arrazy, Teologi Ulama Tasawuf di Nusantara Abad XVII-XIX. Ciputat: Maktabah Darus Sunnah, 2011. Heer, Nicholas, A Concise Handlist of Jawi Authors and Their Works. Washington: n.p, 2009. Ibn Ḥazm, al-Faṣl fī al-Milal wa al-Niḥal. Beirut: Dār al-Ma‘rifah, 1983. Isa, Ahmadi, “Ajaran Tasawuf Syeikh Muhammad Nafis al-Banjari”, thesis Ph.D Jakarta: IAIN Syarif Hidayatullah, 1996. Ismail, Engku Ibrahim, Syeikh Daud bin Abdullah al-Fatani: Peranan dan Sumbangan terhadap Khazanah Islam di Nusantara. Kuala Lumpur: Akademi Pengajaran Melayu University Malaya, 1992. Kalsum, Nyimas Umi, “Tuḥfah Ar-Rāgibīn fī Bayān Ḥaqīqat Īmān al-Mu’minīn”, thesis M.A. Jakarta: University of Indonesia, 2004. Laffan, Michael, The Making of Indonesian Islam. New Jersey: Princeton University Press, 2011. Madjid, Nurcholish, Islam Doktrin dan Peradaban. Jakarta: Paramadina, 2008. Mas'ud, Abdurrahman, Dari Haramain ke Nusantara. Jakarta: Kencana, 2006. McDonald, Duncan, Development of Muslim Theology, Jurisprudence and Constitutional Theory. New York: Charles Scribner’s Sons, 1903. Mulyati, Sri, “Sufism in Indonesia: An Analysis of Nawawi al-Banteni’s Salālim al-Fuḍalā”, thesis M.A. Montreal: University of McGill, 1992. Muttalib, Abdul, “The Mystical Thought of Muhammad Nafīs al-Banjārī: An Indonesia Sufi of the Eighteenth Century”, thesis M.A. Montreal: McGill University, 1995. Nafīs, M. al-Banjārī, Durr al-Nafīs fī Bayān Waḥdat al-Af‘āl wa al-Asmā‘ wa al-Ṣifāt wa al-Dhāt al-Taqdīs. Singapura: al-Haramayn, n.d. Nasution, Harun, Teologi Islam. Jakarta: UI Press, 2011. Palimbānī, ‘Abd al-Ṣamad al-, Sayr al-Sāllikīn ilā ‘Ibādat Rabb al-‘Ālamīn. Singapura: al-Haramayn, n.d. Quzwain, M. Chatib, Mengenal Allah: Suatu Studi Mengenai Ajaran Tasawuf Syekh Abd al-Shamad al-Palimbani. Jakarta: Bulan Bintang, 1985. Rānīrī, Nūr al-Dīn al-, Durrat al-Farā'id bi Sharḥ al-‘Aqā’id, MS collection of PNRI Jakarta. Research Team IAIN Antasari, Risalah Tasawuf Syekh Abdul Hamid Abulung. Banjarmasin: IAIN Antarasari, 2003. Shahrastānī, Muḥammad bin ‘Abd al-Karīm al-, al-Milal wa al-Niḥal. Beirut: Dār al-Kutub al-‘Ilmīyah, 2011. Ṣiddīq, ‘Abd al-Raḥmān al-Banjārī, Fatḥ ‘Ālim fī Tartīb al-Ta‘līm. Singapura: Matba‘ah Ahmadīyah, 1936. Sinkilī, ‘Abd al-Ra’ūf al-, ‘Umdat al-Muḥtājīn ilā Sulūk Maslak al-Mufradīn, MS collection of PNRI Jakarta. Tirmasī, Maḥfūẓ al-, Kifāyat al-Mustafīd Limā 'Alā Min al-Asānīd. Beirut: Dār al-Bashā’ir al-Islāmīyah, n.d. Voorhoeve, P., “Abdul Samad al-Palimbani”, in The Encyclopaedia of Islam. Leiden: Brill, 1967. Zabīdī, Murtaḍā al-, Itḥāf al-Sādāt al-Muttaqīn. Beirut: Dār al-Kutub al-‘Ilmīyah, 2017.